STUDI KUAT TEKAN DAN KUAT LENTUR BETON PADA PERKERASAN KAKU TERHADAP VARIASI SARINGAN AGREGAT KASAR - Riduan, -; Sulandari, Eti; Sumiyatinnah, - (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2017)
Rigid pavement construction is widely used in underlying soil conditions that hasa low bearing capacity, or on a soil with a conditions that has a non-uniform bearing capacity.However, in the fieldsometimes the work implementers had an issue with the limited materials that not meet the specifications that has been planned, so the use of the new materials or the existed materials in the location around are being chosen as an alternative. The methodology of this study is about the study of a compressive strength and flexural strength, with concrete cylinder testand theconcrete beam. The concrete mixtureis planned by using SNI 2002 method with two variations of the filter arrangements whichare a normal filter arrangement and a filter arrangement withoutthe filter with size 9,5 mm. After the test and the study being conducted, the result of the cylinder compressive strength test on concrete using normal filter arrangement yielded an average compressive strength of 41,84 MPa while for concrete using filter arrangement withoutfilter with size of 9,5 mm has an average around 45,11 MPa. The maximum compressive strength is achieved on the variation using both aggregates with an initial plan of 30 MPa. For the use of the filter arrangement without the filterwith size of 9.5 mm isincreased by 7.24%. The result of bending strength test on concrete using normal filter arrangement is around 4.32 MPa and while for the concrete without filter with size 9.5 mm has an average of 4.71 MPa. The maximum flexural strength of the concrete were achieved on the variation using the granules from the aggregate fraction of the sieve with an initial plan of 4 MPa, and while without the filter with size 9.5 mm stretched by 8.28% from the normal aggregate fraction. The stability value on the aggregate fraction of the filter strain without the filter with size of 9.5 mm has a higher compressive strength value than the aggregate fraction of the normal filter arrangement. Hence that the coarse aggregate fraction without 9.5 mm filter are more subtle, so the concrete pores are less formed and have a better density than the normal filter arrangement. Â  Keyword :compressive strength, flexural strength, variation of Â the aggregate filter